A model simulator: The lives of Jay W Forrester. Issue 2 (3rd April 2018) - Lane, David C.; Sterman, John D.
Abstract: Forrester's presence as one of the 23 members of the IFORS "Operational Research Hall of Fame" rests on his creation, development and application of the System Dynamics approach. However, his career also involved highly significant theoretical and applied work in, and contributions to: servomechanisms, computer memory, digital computing technology, flight simulators and defence information systems. Rich and varied as these experiences were, they involve a consistency and commonality of interests and approach. The paper outlines Forrester's life and how his background and early careers led to the creation of System Dynamics.